?OPTIMAL FLOWRATE OF A GAS IN SEMI-BATCH GAS-LIQUID REACTORS - TAL, F.; AHMED, S.; TARIQ, M.A.; HUSSAIN, L. (Biological Sciences - PJSIR, 1994)
The present work deals with the optimisation of the models for slow and fast kinetic regimes in semi-batch gas- liquid reactors. The control variable is taken to be the inlet gas flowrate, the objective is to minimisc the gas consumption when gas ispassed continuously throug aliquid reactant held within the reactor. The main optimisation techniques used for this purpose were Pontryagin's Maximum Principle and Dynamic Programming. The main conclusion which can be drawn is that savings in gas consumption for slow regimes model are much more significant than for the fast regimes model.